Consecuencias sexuales del consumo de pornografía en adolescentes y adultos jóvenes. - Constante Carrasco, Allisson Adamari (2024)
Sexuality frames the expression of thoughts, feelings, and behaviours. It shows the identity of the human being, considering their capabilities, tools of expression, and management of individuality. Pornography constitutes sexually explicit audio-visual material. It shows scenes that generate stimulation and sexual response. This research aims to analyze the sexual consequences of pornography consumption in adolescents and young adults through a transversal and descriptive bibliographic review using inductive-deductive, analyticalsystemic, and historical-logical methods. The researcher gathered information from databases such as PubMed, DOAJ, ProQuest, Scopus, and Scielo. A population of 180 scientific articles was selected and reduced to a sample of 70. These scientific articles were analyzed and evaluated based on their methodological quality through the evaluation instrument for the critical analysis of quantitative research (CRF-QS). The results demonstrate there is a high consumption of pornography from an early age. Consequently, it generates negative sexual consequences in men, such as risky behaviors, the tendency to consume substances, sexualization of contexts and people, and a predisposition to casual sex practices, among others.Similarly, adverse effects were evident among young women that affect self-esteem, reduce relationships, and increase masturbation preferences. However, women present favorable responses regarding the differentiation of content and their sexual development. For this reason, the researchers developed a psychoeducational program to promote sexual health. It was possible to address topics like sexuality, inadequate perception of pornography, and adverse effects of consumption.